Pengaruh Perendaman Paving Block Terhadap Salinitas Air Laut - Thutug Rahardiant Primadi; Ani Listriyana; Nurul Amalia Silviyanti; Wulan Afni Choyriya; Syaifudridzal Syaifudridzal (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2025)
Environmental changes in marine ecosystems due to pollution and synthetic materials are a growing concern. This study investigates the impact of soaking plasbut paving blocks, made from recycled plastic, on seawater salinity. Initial salinity measurements indicated a decrease from 31 % to 27 % after 3 days of immersion, suggesting the absorption of seawater salts by the paving blocks. However, by day 5, salinity began to rise, reaching 46 % by day 15, indicating that the paving blocks released substances that increased salinity. This non-linear interaction highlights a complex relationship between plasbut paving blocks and seawater, where initial salt absorption is followed by the release of ions, such as sodium and chloride, that enhance salinity. The study emphasizes the importance of understanding the long-term effects of using plasbut paving blocks in coastal areas, as changes in salinity could disrupt sensitive marine ecosystems. Further research is recommended to explore the chemical processes involved and the ecological implications of these findings.